Improved Implementation of Nonlinear Analytical Redundancy Relations: Application in Robotics*. Issue 19 (2015) - Villanueva, A.; Verde, C.; Torres, L.
Abstract: This paper copes with the problem of detecting actuators' faults in a two-degree of freedom robot manipulator by using nonlinear analytical redundancy relations composed by derivatives of known signals. To generate the residuals, the redundancy relations are handled with two procedures. The first one allows the determination of a transformation of the base relations to reduce by one the order of the involved derivatives. The second one directly estimates the derivatives of the measurements by using a uniform robust exact differentiator. Simulation results are presented to show the robustness of the nonlinear analytical redundancy relations by using the transformation procedure even in the case of noisy measurements.